Turbulent burning rates of gasoline components, Part 1 – Effect of fuel structure of C6 hydrocarbons. (1st March 2016) - Burluka, A.A.; Gaughan, R.G.; Griffiths, J.F.; Mandilas, C.; Sheppard, C.G.W.; Woolley, R.
Abstract: Measurements of laminar and turbulent burning velocities have been made for premixed hydrocarbon-air flames with six carbon atoms including unsaturated, branched and cyclic molecules. The seven different fuels studied were n-hexane, 1-hexene, 1-hexyne, 2, 2 dimethyl butane, 2 methyl pentane (isohexane), cyclohexane and cyclohexene. The tests were performed in a constant volume, optically accessed spherical bomb, with the use of the schlieren technique and a high-speed camera. The deflagrations were initiated at elevated pressure and temperature of 0.5 MPa and 360 K, where burning velocity data is relatively sparse, under laminar and turbulent conditions with rms turbulent velocities of 2 and 6 m/s and for equivalence ratios of 0.78–1.67. The primary objective of this work was to compare the turbulent burn rates of the different fuel–air mixtures; the laminar burning velocities were used to interpret the turbulent data. The ranking of the laminar burning velocity was overall found to be 1-hexyne > cyclohexene > 1-hexene > cyclohexane > n-hexane > 2-methyl pentane > 2, 2 dimethyl butane for the range of equivalence ratios tested. The ranking was found to be the same for the turbulent burn rate measurements, particularly so for the slowest and fastest fuels. As the rms turbulent velocity increased the relative differences between the fuels were found to generally increase for lean mixtures, remain similar around stoichiometric equivalence ratio and decrease for rich mixtures. This behaviour was linked to the sensitivity of turbulent flames to stretch and thermo-diffusive stability.